KONTEKSTUALISASI KONSEP NEGARA MADINAH SEBAGAI PETA JALAN INDONESIA EMAS 2045 - Muhammad Sabri (PRODI HUKUM TATANEGARA, 2025)
This study seeks to answer the research question: how can the contextualization of the Medina State concept serve as a reference in developing a roadmap toward Golden Indonesia 2045? This question arises from the fact that, despite its abundant resources, Indonesia remains a developing country and thus requires a strong national strategy. The research employs a qualitative approach using library research, drawing upon classical sources such as Sirah Nabawiyah by Ibn Hisham, Tarikh al-Tabari, as well as contemporary literature on Islamic politics and national development. The data were analyzed interpretively to identify the relevance of Medina’s political values to the modern Indonesian context. The findings reveal four key principles derived from the Medina State that are highly relevant for Indonesia: (1) universal education through formal and non-formal institutions as human capital development; (2) professional leadership by entrusting affairs to experts; (3) constitutional commitment, as exemplified in the Charter of Medina; and (4) social unity that fosters national optimism. These principles can be employed both conceptually and practically in formulating strategies toward Golden Indonesia 2045. The impact of this study lies in its contribution to academic discourse on the intersection of Islamic values and national development, while also offering practical insights for strengthening governance that is just, inclusive, and globally competitive.